DERIVATIONAL AFFIXES ON NATIONAL COLUMN IN THE JAKARTA POST ONLINE NEWSPAPER - Yulfi Yulfi; Ayu Oktaviyani (EDULIA: English Education, Linguistic and Art Journal, 2021)
This aims of this research were to find out the kinds and the process of derivational affixes of national column in The Jakarta Post online. This research belong to descriptive qualitative research. The data was gotten from national column of The Jakarta Post online newspaper which published on June 4th - 8th 2018. The data in this research were collected by some steps 1) searching The Jakarta Post Newspaper at www.newspaperPDF.com, 2) reading the sentences of the chosen in The Jakarta Post Online Newspaper to find out the words which contain derivational affixes, 3) collecting the words which contain derivational affixes to get the data of the kind derivational affixes by prefixation and suffixation. The result of analysis in this research were 1) The total number of words that conducted by a process of derivational affixes are 301 words were suffixes forming noun are more dominantly as much as 167 words which a process of verb to noun are frequently found in a 123 times, 2) The derivation process of suffixes is much more found from the derivational prefixes. Keyword: Affixes, Derivation, The Jakarta Post Online Newspaper